Implementasi Konsep Konservasi Air di Gedung Apartemen X - Vine Valenia David; Kancitra Pharmawati; Djoni Kusmulyana Usman (Fakultas Teknik, 2019)
Clean water crisis that occurred in Bandung is caused by land conversion in North Bandung area which is a recharge area into commercial buildings. This increases runoff rate from 40% to 70% that can lead can lead to flooding and reduced groundwater availability. Therefore, it is necessary to save water by implementing water conservation. Considering those problems, this study aims to apply the concept of water conservation in X Apartment building that is located in the North Bandung Region by referring to Mayor Regulation of Bandung in 2016. Water conservation efforts that will be applied are wastewater reuse into water recycle, rainwater harvesting, infiltration well construction and placing water meters. The application of water conservation concept considers two conditions, namely in rainy season and dry season. Total need for clean water can be saved by 45,8% in dry season, while in rainy season clean water can be saved by 31,74%.